History of Oral Mucosal Lesions in Oral Squamous Cell Carcinoma Patients - Keinänen, Arvi; Snäll, Johanna; Hagström, Jaana; Uittamo, Johanna (Quintessence Publishing, 2026)
Purpose: To evaluate the occurrence of previous mucosal dysplasia in patients with oral squamous cell carcinoma (OSCC) and to charaterise patient profile, types of previous oral mucosal lesions, and care-seeking in relation to earlier mucosal findings.
Materials and methods: Retrospective data of OSCC patients with a primary tumour were collected. The primary outcome variable was any history of oral mucosal findings; the secondary outcome variable was a history of previous oral mucosal dysplasia. The primary predictor variable was the mode of seeking treatment. Patient and tumour-related variables were compared between patients with and without anamnestic mucosal changes or findings.
Results: A total of 528 patients were included in the study. Of these patients, 169 (32.0%) had a history of an oral mucosal lesion. Oral mucosal dysplasia was detected in 34 patients (6.4%) before the OSCC diagnosis. Patients who had a history of heavy alcohol use were less likely to have a history of any mucosal lesions or dysplasia (adjusted odds ratio [aOR] 0.350, 95% confidence interval [CI] 0.215-0.571, p 0.001 and aOR 0.235, 95% CI 0.070-0.795, p = 0.020). Tumours were detected more often in conjunction with routine appointments in patients with a history of any mucosal lesions (aOR 2.671, 95% CI 1.704-4.187, p 0.001) and in those with previously detected dysplasia (aOR 6.195, 95% CI 3.004-12.774, p 0.001).
Conclusions: The results emphasise the importance of careful examination and close follow-up of findings in the oral mucosa.